Realni potencial za lokalno oskrbo s hrano v Sloveniji - Perpar, Anton (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2010)
The degree of self-sufficiency with food products in Slovenia has decreased in the last years, for some products even bellow one half. In the article the qualitative analyses of possibilities for self-sufficiency improvement are presented. They are based on comparative analysis of production potentials of agricultural land, projection of the development trends in agriculture and agricultural land use and trends in food consumption. An analysis of good practices with local food supply and results of MOLAND model (simulating possible future agricultural land use on the basis of different possible future development scenarios) are added as well.
Keywords: agriculture; hrana; kmetijska zemljišča; kmetijstvo; lokalne skupnosti; oskrbovalne verige; Slovenia; Slovenija